Analysis of Water Quality in Asmoroqondi Beach, Palang District, Tuban Regency using the Principal Component Analysis (PCA) method - Mudloifah, Istatik; Purnomo, Tarzan (LenteraBio : Berkala Ilmiah Biologi, 2023)
Analysis of water quality is a study of water conditions in terms of physical, chemical, and biological parameters. This study aims to determine the quality of the waters at Asmoroqondi Beach based on quality standards and to analyze the distribution of water quality parameters at Asmoroqondi Beach using the Principal Component Analysis (PCA) method. This research includes the type of exploratory descriptive research. Measurement of water quality parameters was carried out on 5 transects with 3 repetitions for each transect, namely at a depth of 0-meter, 50-meter depth, and 150-meter depth. Water quality parameters measured include temperature, brightness, current velocity, salinity, pH, and dissolved oxygen (DO). Data analysis was carried out in a quantitative descriptive manner. Water quality data were compared with quality standards and analyzed using the Principal Component Analysis (PCA) method. The results showed that the quality of the waters at Asmoroqondi Beach was classified as unfavorable with 3 detected parameters that were not by the quality standards, namely brightness, salinity, and DO. The distribution of water quality parameters shows that transect I is characterized by current velocity and salinity, transect II is characterized by DO and temperature, transect III is characterized by brightness, transect IV is characterized by pH, while transect V does not have the strongest marker. Thus it can be concluded that the water quality status at Asmoroqondi Beach is included in the unfavorable category for the survival of marine biota. Keywords: brightness; dissolved oxygen; pH; salinity; temperature